A bridge too far - Ryan, Cornelius (New York : Simon and Schuster, 1974)
Reviews the individuals, tactics, and events involved in Field Marshal Bernard Law Montgomery's plan to end World War II.
Operation Market-Garden, September 17-24, 1944 -- The retreat -- The plan -- The attack -- The siege -- Der Hexenkessel -- A note on casualties -- The soldiers and civilians of a bridge too far what they do today.
Maps on lining papers.
Includes bibliographical references (pages 641-649) and index.
105510
Keywords: 1944; World War, 1939-1945.; Arnhem, Battle of, 1944.; Netherlands -- Arnhem